Intensitas Serangan Hama Ulat Daun (Plutella xylostella) dan Populasi Serangga pada Kubis Bunga Kultivar Larissa F1 dengan Perlakuan Pestisida Nabati - Camelia Grecia Ariyanti; Siti Latifatus Siriyah; Rommy Andhika Laksono (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2025)
Cauliflower cultivation faces various challenges, one of which is pest infestation. Farmers commonly use synthetic pesticides for pest control, but their excessive use negatively impact the human health and the environment. Therefore another alternative, environmentally friendly control methods, such as botanical pesticides, are needed. This study aimed to evaluate the effect of botanical pesticides on pest attack intensity and insect population dynamics in cauliflower. The experiment was conducted using a single-factor Randomized Block Design (RBD) consisting of 5 treatments and 5 replicates: K (control), P (papaya leaves), M (neem leaves), S (soursop leaves), and T (synthetic pesticides). Insect sampling was taken 4 times at 1-8 wap with an interval of 14 days, using slope pitfall trap, yellow sticky trap, and sweep net. Data were analyzed using analysis of variance (ANOVA) and a 5% BNT test. A total 32.418 individual insects, consisting of 12 orders, 58 families, and 91 morphspecies. The results showed that botanical pesticides significantly affected the average intensity of cabbage leafworm infestation at 4, 6, and 8 wap,. Synthetic pesticides reduced cabbage leafworm infestation to 0,000% as the lowest values compared to other treatments.